(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2023)
This article presents a systematization of experiences, based on the agreement between the Universidad Abierta para Adultos (UAPA) and the Procuraduría General de República Dominicana, to bring distance and virtual higher education to the prisons of the Cibao region. The systematization involved organizing institutional information on the origins of the training program and its progress to the present. In addition, interviews with prisoners subject to the programs to understand the meanings produced by them about the education they receive, through the use of virtuality. It is proposed, among other actions, to have a basic document to support the possibility that the Universidad Estatal a Distancia (UNED), of Costa Rica, can implement the virtual modality in its educational programs in prisons of that country. The scope has to do with two prisons with inmates who are in the virtual education system of the UAPA, in some graduate program. The results show the qualitative assessment that inmates give to the virtual education they receive.